THE ROLE OF GROUP COHESION AS A MEDIATOR VARIABLE ON GROUP PERFORMANCE - Suwangsih, Iwang; Suhariadi, Fendy; Ratmawati, Dwi; Supriharyanti, Elisabeth (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2025)
The goal of this study is to investigate the role of group cohesion as a mediator variable on the influence of group bonding and group norms on group performance. It is necessary to study group performance because good group performance is very important for the organization, which consists of many groups. This research was conducted at the Setia Bhakti Women's Cooperative, which consists of 470 groups, and the sample for this research was 320 groups. This research uses a quantitative approach and uses structural equation models to test the role of group cohesion. This study finds that group cohesion as a mediator variable has an important role, because the effect of group bonding on group performance is significant if it is mediated by group cohesion. Likewise, the relationship between group norms and group performance will be significant if it is mediated by group cohesion. This study contributes to expanding the meaning of important antecedents of group performance through group cohesion. This study also enriches the literature on group performance by using the social capital theory framework because previous research used social network theory.